ESTABLISHMENT OF THE CORRELATION DEPENDENCE OF MASTERING BASIC EXERCISES IN SPORTS ACROBATICS ON THE USE OF INDIVIDUAL SPECIAL PREPARATORY EXERCISES BY YOUNG ACROBATS 6-7 YEARS OLD - Tetiana Chernykh; Viacheslav Mulyk (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the correlation relationship between the basic exercises of the initial training of young acrobats and special preparatory exercises used to master them. Material and Methods: the research was carried out on the basis of the complex children's sports school No. 6, Slobodsky district of Kharkov. 14 children 6-7 years old took part in the study, they were engaged in sports acrobatics in sports and health-improving groups, for whose participation parental consent was obtained. At the beginning of the study, after introductory sessions, control testing of the basic exercises "swallow", "forward roll", "wheel", "birch" "crab position", development of motor qualities, necessary for the fulfillment of the specified basic exercises, and repeated testing was carried out, the assessment of which was carried out on a 10-point scale. After that, a correlation analysis of the dependence of basic acrobatic exercises on special preparatory exercises that were used to perform them was carried out. Results: in the process of using complexes of special preparatory exercises, the quality of basic exercises performance was increased due to the use of special preparatory exercises in the "swallow" exercise (t=3,94; p<0,001), "forward roll" (t=2,90; p<0,05), "wheel" (t=2,12; p<0,05), "birch" (t=2,67; p<0,05), "crab position" (t=2,59; p<0,05). Conclusions: as a result of the research, a correlation has been established between basic acrobatic exercises and individual special preparatory exercises used during their training.